2004
DOI: 10.1080/10428190310001646879
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Natural Killer Cell Leukemia/Lymphoma: Case Report, use of Telesynergy™ and Review of the Literature

Abstract: Natural killer cell malignancies, although increasingly recognized, remain rare tumors within the USA and Europe. They are somewhat more common in Asia, and have been best characterized within this population. We present a case of a young Caucasian woman who presented acutely with an aggressive natural killer cell leukemia/lymphoma. Use of Telesynergy technology enabled a transatlantic telemedicine conference with colleagues in a center of expertise. Unfortunately the patient was ultimately refractory to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…21 Rare sporadic cases occur in Western populations. 36 There had been uncertainty as to whether ANKL, similar to extranodal NK/T lymphoma, is an EBV-associated disorder. Recent studies have confirmed positivity for EBV in both endemic and nonendemic populations.…”
Section: Aggressive Nk-cell Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…21 Rare sporadic cases occur in Western populations. 36 There had been uncertainty as to whether ANKL, similar to extranodal NK/T lymphoma, is an EBV-associated disorder. Recent studies have confirmed positivity for EBV in both endemic and nonendemic populations.…”
Section: Aggressive Nk-cell Leukemiamentioning
confidence: 99%
“…Recent studies have confirmed positivity for EBV in both endemic and nonendemic populations. 34,[36][37][38] Despite similarities in phenotype and genotype, clinical and morphologic features distinguish these two disorders. 39 First, ANKL is an aggressive disorder with a poor prognosis, irrespective of treatment.…”
Section: Aggressive Nk-cell Leukemiamentioning
confidence: 99%
“…Comparatively, based on the Japanese survey of NK-cell neoplasms diagnosed from 1994 to 1998 [36], the NK-cell Tumor Study Group reported on a Japanese series of 172 NK-cell tumors, which included 22 ANKCL (12.8%) [37]. Few European series of NKTCL were published to date [38,39] and, in Europe, reports on ANKCL are limited to sporadic cases [40-43]. …”
Section: Reviewmentioning
confidence: 99%
“…Successful treatment with alemtuzumab has been reported in the subtypes of mature T-cell neoplasms, such as Lennert's lymphoma [31], hepatosplenic gammadelta T-cell lymphoma [32], angioimmunoblastic T-cell lymphoma [33] and primary cutaneous CD30-negative CD8-positive cytotoxic large T-cell lymphoma [34]. Data of its application in aggressive NK-cell leukemia/lymphoma is scanty with possible potential efficacy [35,36]. However, its combination with chemotherapy is more likely leading to more sustain and higher response rate in view of the aggressiveness of the disease.…”
Section: Introductionmentioning
confidence: 99%